A psychometric investigation into the Turkish version of the SLEEP-50 Questionnaire - Abdullah Yildirim; Selahiddin Ogulmus; Onur Yilmaz; Murat Boysan (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
The aim of the study is to investigate the psychometric properties of the Turkish version of the SLEEP-50 Questionnaire (SLEEP-50), designed to assess probable caseness of sleep disorders in general population based on the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition Text Revision. Five hundred and twenty-two college students, aged between 18-44 years, participated in the study. Using the cutoff values informed by initial validation study, we detected the prevalence rates of sleep disorders. Internal consistency and test-retest reliability of the SLEEP-50 were evaluated. The Pittsburgh Sleep Quality Index (PSQI) was administered along with the questionnaire to assess convergent validity. The internal consistency of the overall questionnaire was excellent (Cronbachs α=.91). Substantial kappa values showed that temporal stability of the SLEEP-50 was adequate. All sleep disorders detected by the SLEEP-50 were found to be significantly associated with the poor sleep quality as indexed by the PSQI. The Turkish version of the SLEEP-50 revealed adequate psychometric properties. [JCBPR 2018; 7(3.000): 127-132]